2013
DOI: 10.1177/1538574413510618
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Amputation and Revascularization

Abstract: This study investigates whether ethnic minorities presenting with critical limb ischemia (CLI) are more likely to undergo major limb amputation compared to white patients. The Nationwide Inpatient Sample (NIS) database was used to identify all patients admitted with CLI; lower extremity revascularization; and major lower extremity amputation from 1998 to 2005. The NIS identified 240 139 patients presenting with CLI--68.2% white, 19.5% black, 9.0% Hispanic, and 1.24% Asian. In all, 83 328 patients underwent rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 24 publications
0
29
2
Order By: Relevance
“…The presence of fissures, ulcers (having a lifetime risk of about 25%), or refractory infections may result in foot amputation; it has been estimated that a lower limb is lost every 30 s as consequence of diabetes [1]. Known risk factors for amputation include advanced age, increased duration of diabetes, male gender, certain ethnicities, poor glycemic control, and lack of preventive care [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fissures, ulcers (having a lifetime risk of about 25%), or refractory infections may result in foot amputation; it has been estimated that a lower limb is lost every 30 s as consequence of diabetes [1]. Known risk factors for amputation include advanced age, increased duration of diabetes, male gender, certain ethnicities, poor glycemic control, and lack of preventive care [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the disparities persisted after adjustment for age, sex, and social class (considers income and employment). In a similar study, Hughes et al [25] studied a population of 240,139 patients from the Nationwide Inpatient Sample (NIS) database who presented with critical limb ischemia. Black patients made up 20 % of the total patient sample, however represented 25 % of the total lower extremity amputations performed.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings suggest that significant health insurance status disparities exist in the use of spine augmentation procedures, findings consistent with the already reported disparities in access to health care by minorities and the uninsured. 5,[10][11][12][13][14][15] These current findings are potentially clinically relevant because prior studies have shown that patients receiving spine augmentation procedures demonstrate improved survival and quality of life compared with patients receiving nonoperative treatment. 16,17 In a study of the 2006 Medicare Provider Analysis and Review File data base, Chen et al 16 demonstrated that patients who underwent vertebroplasty and kyphoplasty had significantly higher 3-year survival rates compared with patients receiving nonoperative management.…”
Section: Discussionmentioning
confidence: 87%